A configurable approach for intra-model inconsistency management in multi-view collaborative modeling - Alsharuee, Hayder Ali Neamah; Sharbaf, Mohammadreza; Tork Ladani, Behrouz (Frontiers in Computer Science, 2026)
IntroductionIn the software development life cycle, collaborative modeling through multiple projective views of a single, shared model is a critical activity that enables effective collaboration among experts and stakeholders. Real-time optimistic collaboration in multi-view modeling allows concurrent modifications but often introduces inconsistencies that must be resolved to achieve an integrated and valid model. Existing inconsistency management methods frequently focus on isolated repairs or offer limited alternatives, lacking support for collaborative dynamics and configurable resolution strategies. This study aims to develop a configurable framework for managing intra-model inconsistencies in real-time multi-view collaborative modeling environments.MethodsWe propose a novel framework for inconsistency management tailored to multi-view collaborative modeling, based on Model-Driven Engineering (MDE) principles. The framework supports real-time modeling scenarios and enables change propagation according to the online collaboration mode. Key components include a consistency oracle and incremental consistency checking, which together manage the integration of model changes and overlaps. We introduce the COMIM approach, which assists collaborators in handling inconsistencies by considering team interactions, individual ownership, and configurable repair strategies.ResultsThe framework was evaluated through a case study involving multi-view collaborative modeling sessions. Empirical results demonstrate the feasibility and effectiveness of the COMIM approach in maintaining consistency during concurrent modeling activities. The system performed efficiently for teams of up to seven concurrent users, successfully managing change propagation, detecting inconsistencies incrementally, and supporting configurable resolution aligned with collaborative priorities.DiscussionThe proposed framework effectively addresses the complexities of repairing inconsistencies across diverse software models in a collaborative setting. By emphasizing collaborative dynamics, our approach advances traditional inconsistency management methods, which often lack personalization and configurability. Future work may explore scalability to larger teams and adaptation to additional modeling paradigms.